Typical mechanisms of degradation of thermoelectric materials and ways to reduce their impact on the reliability of thermoelectric modules - Gorskyi, Petro (Physics and Chemistry of Solid State, 2022)
The review considers a number of typical mechanisms of degradation of thermoelectric materials in the process of their functioning as a part of thermoelectric generator modules. Among them are diffusion and self-diffusion in thermoelectric materials and contact structures, loss of dopants by thermoelectric materials due to sublimation, formation of intermetallic compounds in contact structures, accumulation of structural defects under the influence of thermal and mechanical loads, mechanical destruction of thermoelectric legs, contact structures and other structural members of modules, chemical interaction of thermoelectric materials with other structural members. The main design and technological ways and methods of reducing the negative impact of these mechanisms on the reliability of thermoelectric materials and modules are also considered.